Diagnóstico de aberrações ópticas em um sistema óptico adaptativo - Antonio Isidorio Ferreira Junior (2006)
diagnosis of low-order optical aberrations decomposed over Zernike polynomials and also the coupling of a custom CMOS wavefront sensor to a micromachined adaptive mirror in an adaptive optical system. The algorithm does not rely on a xed basis matrix -as opposed to traditional methods-, offers excellent immunity to the propagation of round-off errors and admits real-time input dimension adaptability to speed up computations.